Nuclear Magnetic Resonance Spectroscopy: (13)C Spectra of Some Common Nucleotides - Dorman, Douglas E. (1970)
Natural-abundance (13)C nuclear magnetic resonance spectra of ten common nucleotides in neutral, aqueous solutions have been determined and interpreted. The spectra of two of these substances were also determined in acidic solutions, and several of the carbon chemical shifts were found to depend markedly on pH. Within the limited range of concentrations employed, there were observed no carbon chemical-shift changes which could be ascribed to base-stacking or base-pairing phenomena.